Oral Ulcers Induced by Cytomegalovirus Infection: Report on Two Cases - Ribas, Renata; de Lima, Antonio Adilson Soares (UI Scholars Hub, 2017)
Human cytomegalovirus (CMV) is a virus that can compromise the lungs and the liver and cause infection in the gastrointestinal tract. In addition, this virus can cause infectious mononucleosis syndrome, infection in the CNS, and retinitis. Moreover, it has been associated with the development of oral hairy leukoplakia and ulcers. Objective: To report two cases of patients with HIV with oral manifestations associated with CMV infection. Case Report: In the first case, the patient sought medical attention, with complaints of weakness, fever, cough, and weight loss. In the second case, the patient complained of weakness and blurred vision for about a week. Both patients were infected with HIV and made irregular use of antiretroviral therapy. Several ulcers were observed in the mouth that caused much discomfort. The diagnosis of CMV infection was defined by the following tests: enzyme immunoassay fluorescence-CMV IgG and PCR for CMV in real time. Ganciclovir has been used in the treatment of patients, and oral ulcerations received symptomatic treatment. Conclusion: The dentist must be aware that CMV may also be responsible for the development of ulcers in the oral cavity, especially in immunocompromised patients.